Patients' characteristics and 30-day mortality for those undergoing elective surgeries during the COVID-19 pandemic in Bangladesh. - Shakera Ahmed; Anwarul Karim; Tanvir Kabir Chowdhury; Orindom Shing Pulock; Nowrin Tamanna; Mastura Akter; Puja Biswas; Fahmida Afroz; Susmita Dey Pinky; Anika Nahrin Alabbi; Tasnuba Raisa Jamil; Zarin Tasnim; et al. (PLoS ONE, 2023)
Background The COVID-19 pandemic has significantly impacted the surgical practice throughout the world, including elective surgical care. This study investigated the characteristics of patients undergoing elective surgery, the prevalence of COVID-19 infection, the surgical procedures performed, and 30-day mortality in general and pediatric surgical settings in selected tertiary-level hospitals in Bangladesh from November 2020 to August 2021. Methods This serial cross-sectional study included 264 patients scheduled for elective surgeries during the study period. All patients underwent COVID-19 real-time polymerase chain reaction (RT-PCR) testing within 24 hours before surgery. Data on age, sex, common comorbidities, surgical procedures, and 30-day mortality were collected and analyzed. Furthermore, comparisons were made between COVID-19 positive and negative patients. Results The prevalence of COVID-19 infection among patients was 10.6%. Older age, a history of major surgery within the last three months, hypertension, and diabetes mellitus were significantly associated with COVID-19 infection. All COVID-19-negative patients underwent surgery, while only 46.4% of COVID-19-positive patients underwent surgery. The most common surgical procedures were related to the digestive system, breast, and urinary system. Only one patient (0.4%) died within 30 days after surgery among the COVID-19-negative patients, whereas two patients (7.1%) died among the COVID-19-positive patients: one before surgery and one after surgery. Conclusions This study provides valuable insights into the characteristics, burden of COVID-19 infection, and 30-day mortality of patients undergoing elective surgery in tertiary care centers in Bangladesh during the pandemic.